Crotalaria phulei (Fabaceae): A new species from Nagpur (MS), India - Chaudhary, Rupali Ramesh; Gadpayale, Jagannath V.; Somkuwar, Subhash R. (Phytotaxa, 2026)
Crotalaria phulei a new species described and illustrated from the Khairi Butibori–Umred Forest, Nagpur District, Maharashtra, India. The species shows morphological affinity to C. juncea and C. shrirangiana, which occur in the Western Ghats and eastern Peninsular India, typically along forest edges and cut slopes of hillocks. Crotalaria phulei is distinguished from these taxa by a combination of vegetative and reproductive features, including stipules, bracts and bracteoles, inflorescence, calyx, standard petal, stamens, pedicel, pods, and seeds. Based on these characters, the species is assigned to Crotalaria sect. Crotalaria. The description is supported by detailed photographic illustrations, an identification key to allied species, and a preliminary assessment of conservation status. The discovery highlights the continued diversity of Crotalaria in central India and the importance of systematic exploration of its forest habitats.